2017
DOI: 10.1021/acs.jpca.7b08505
|View full text |Cite
|
Sign up to set email alerts
|

Azines as Electron-Pair Donors to CO2for N···C Tetrel Bonds

Abstract: Ab initio MP2/aug'-cc-pVTZ calculations were performed to investigate tetrel-bonded complexes formed between CO and the aromatic bases pyridine, the diazines, triazines, tetrazines, and pentazine. Of the 23 unique equilibrium azine:CO complexes, 14 have planar structures in which a single nitrogen atom is an electron-pair donor to the carbon of the CO molecule, and 9 have perpendicular structures in which two adjacent nitrogen atoms donate electrons to CO, with bond formation occurring along an N-N bond. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Also, the CO2 molecule has been the subject of investigation from the theoretical point of view [29,34,35]. Our previous studies concerning A•••B complexes with B being CO2 are reported in references [36][37][38][39][40][41]. Simulation of phosphorous/boron frustrated lewis pair complexes (FLP) with CO2 in explicit solvent proposed a two-step mechanism [42].…”
Section: Resultsmentioning
confidence: 99%
“…Also, the CO2 molecule has been the subject of investigation from the theoretical point of view [29,34,35]. Our previous studies concerning A•••B complexes with B being CO2 are reported in references [36][37][38][39][40][41]. Simulation of phosphorous/boron frustrated lewis pair complexes (FLP) with CO2 in explicit solvent proposed a two-step mechanism [42].…”
Section: Resultsmentioning
confidence: 99%
“…Analogous to the venerable and thoroughly studied H-bond [1][2][3] , it is now well accepted that the bridging proton can be replaced by any of a litany of larger atoms, without compromising the strength of the interaction [4][5][6][7] . These substitute atoms are typically electronegative ones, drawn from the right side of the periodic table.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest to explore interactions that are important in biochemical reactions, such as those between azines and azoles with CO 2 . In a previous paper, we presented the structures, binding energies and other properties of CO 2 : azine complexes stabilized by N···C tetrel bonds [ 24 ]. The azoles have pyridine-like N atoms in positions 2, 3, 4 and 5 that may act as electron-pair donors as do the azines.…”
Section: Introductionmentioning
confidence: 99%